Human Choice Predicted by Obtained Reinforcers, Not by Reinforcement Predictors - Stagner, Jessica P.; Edwards, Vincent M.; Bond, Sara R.; Jasmer, Jeremy A.; Southern, Robert A.; Bodily, Kent D. (Frontiers in Psychology, 2020)
Macphail (1985) proposed that “intelligence” should not vary across vertebrate species when contextual variables are accounted for. Focusing on research involving choice behavior, the propensity for choosing an option that produces stimuli that predict the presence or absence of reinforcement but that also results in less food over time can be examined. This choice preference has been found multiple times in pigeons (Stagner & Zentall, 2010; Zentall & Stagner, 2011; Laude, Stagner, & Zentall, 2014), and has been likened to gambling behavior demonstrated by humans (Zentall, 2014; Zentall, 2016). The present experiments used a similarly structured task to examine adult human preferences for reinforcement predictors and compared findings to choice behavior demonstrated by children (Lalli, Mauro, & Mace, 2000), monkeys (Smith & Beran, 2017; Smith, Beran, & Young, 2020), dogs (Jackson, Gordon, MacPherson, Martin, & Roberts, 2020), rats (Chow, Smith, Wilson, Zentall, & Beckman, 2017; Cunningham & Shahan, 2019; Jackson et al., 2020), and pigeons (Roper & Zentall, 1999; Stagner & Zentall, 2010). In Experiment 1, adult human participants showed no preference for reinforcement predictors. Results from Experiment 2 suggest that not only were reinforcement predictors not preferred, but that perhaps reinforcement predictors had no effect at all on choice behavior. Results from Experiments 1 and 2 were further assessed using a generalized matching equation, the findings from which support that adult human choice behavior in the present research was largely determined by reinforcement history. Overall, the present results obtained from human adult participants are different than those found from pigeons in particular, suggesting that further examination of Macphail’s (1985) hypothesis is warranted.